Caledomus gen. nov., a new cillaeine genus (Coleoptera, Nitidulidae) from New Caledonia and taxonomic notes - Kirejtshuk, Alexander G.; Kovalev, Alexey V. (Zootaxa, 2017)
Caledomus extraordinarius gen. et sp. nov. of the subfamily Cillaeinae is described from New Caledonia (Tinchialit). This new genus is a member of the Adocimus-complex of genera. The new name Brittonoma nom. nov. is proposed for the junior homonym Brittonema Kirejtshuk, 2011, non Thorne, 1967.